RNase E cleavage in the atpE leader region of atpE/interferon-beta hybrid transcripts in Escherichia coli causes enhanced rates of mRNA decay - Gross, G. (The Journal of biological chemistry, 1991)
Chimeric transcripts containing the ribosome binding site of the Escherichia coli atpE gene and variants of the human structural interferon-beta gene are subject to RNase E processing in the 5'-untranslated atpE part of the transcripts. The absence of processing at two sites in the atpE leader-sequence caused by the RNase E deficiency in E. coli host N3431 leads to a considerable stabilization of the mRNA moiety. RNase E has originally been described as a processing enzyme for non-mRNAs such as precursor 5 S rRNA and RNA1, but cleavage mRNA substrates have also been reported. RNase E processing of the atpE gene leader sequence-containing transcripts leads to an increased rate of mRNA breakdown. The two RNase E-dependent processing sites in the atpE part of the mRNA transcripts exhibit some similarity to the other known RNase E processing sites. The influence of RNase E cleavage upon post-transcriptional regulation such as RNA stability and the efficiency of translational initiation is discussed.